Some Quantitative Aspects of the Economics Journal Literature - Quandt, Richard E. (Journal of Political Economy, 1976)
The paper investigates various aspects of citation practices on the basis of all citations appearing in full volumes of eight principal journals at 10-year intervals. The growth of the number of citations is in good agreement with the findings for other fields, and the mean age of citations declines over time by about 6 months per decade. Most journal articles have a significant tendency to cite other articles published in the same journal, and the cross-reference patterns are employed to rank the journals in terms of importance. An examination of the list of most frequently cited authors reveals that Nobel prizewinners are characteristically on at least one, but most often more than one, list (a decade apart) and permits tentative predictions as to who future prizewinners will be.